Inequity of Access: Scoping the Barriers to Assisted Reproductive Technologies - Amanda Mackay; Selina Taylor; Beverley Glass (MDPI AG, 2023)
Infertility impacts millions of people of reproductive age worldwide, with approximately 10-15% of couples affected. When infertility is present, there are many potential barriers to treatment, leading to inequity of access. Assisted reproductive technologies (ART) are the mainstay of medical treatment for infertility and include procedures such as in vitro fertilisation. This scoping review aims to explore the barriers to accessing assisted reproductive technologies to highlight a potential role for the pharmacist in addressing these barriers. Five databases, including CINAHL, Emcare, Medline, Scopus, and Web of Science, were searched using keywords that resulted in 19 studies that explored barriers to initially accessing or continuing ART. Studies identified more than one barrier to accessing ART, with the most mentioned barrier being the geographic location of the patient, with others themed as psychological, financial, minority groups, educational level, and the age of the patient. Recommendations were made to address barriers to accessing ART, which included changes to government regulations to increase health education and promotion of infertility. Pharmacists' accessibility, even in geographically remote locations, places them in an ideal position to address many of the challenges experienced by people accessing infertility treatment to improve outcomes for these people.